Amy & Roger's epic detour - Matson, Morgan (Simon & Schuster BFYR, 2010)
After the death of her father, Amy, a high school student, and Roger, a college freshman, set out on a carefully planned road trip from California to Connecticut, but wind up taking many detours, forcing Amy to face her worst fears and come to terms with her grief and guilt.